Sevoflurane-induced pica in female rats - Kouichi Yamamoto; Emiri Yamamoto; Toru Sugimoto; Takuya Sagakami; Atsushi Yamatodani (Elsevier, 2016)
We examined the effects of volatile anesthetics on pica, which can be used to assess nausea and vomiting in rats. We found that inhalation anesthesia with sevoflurane significantly induced pica in female but not male rats. Among the female rats, young rats (8 weeks old) were more susceptible to its induction than adult rats (20 weeks old) with ovariectomy or sham-surgery. Anti-emetic drugs that are used to prevent postoperative nausea and vomiting (PONV) inhibited the pica. These results suggest that sevoflurane-induced pica in young female rats has the potential to be an animal model of PONV in humans.